2012
DOI: 10.1242/jcs.092676
|View full text |Cite
|
Sign up to set email alerts
|

Apico-basal elongation requires a drebrin-E–EB3 complex in columnar human epithelial cells

Abstract: SummaryAlthough columnar epithelial cells are known to acquire an elongated shape, the mechanisms involved in this morphological feature have not yet been completely elucidated. Using columnar human intestinal Caco2 cells, it was established here that the levels of drebrin E, an actin-binding protein, increase in the terminal web both in vitro and in vivo during the formation of the apical domain. Drebrin E depletion was found to impair cell compaction and elongation processes in the monolayer without affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 46 publications
(38 reference statements)
4
37
0
Order By: Relevance
“…The enrichment of protein catabolic pathways is consistent with smoke-exposure studies in alveolar cells that have demonstrated increased endoplasmic reticulum stress and protein degradation [20]. The role of actin and cytoskeletal processes in response to smoking is less well understood, but cytoskeletal-associated pathways containing genes such as ACTN1 and DBN1 have been associated with roles in immune cell activation [21] and columnar epithelial cell function [22]. These data point to further avenues for investigation of the specific nature of inflammatory, catabolic, and cytoskeletal responses in circulating immune cells in smokers.…”
Section: Discussionsupporting
confidence: 59%
“…The enrichment of protein catabolic pathways is consistent with smoke-exposure studies in alveolar cells that have demonstrated increased endoplasmic reticulum stress and protein degradation [20]. The role of actin and cytoskeletal processes in response to smoking is less well understood, but cytoskeletal-associated pathways containing genes such as ACTN1 and DBN1 have been associated with roles in immune cell activation [21] and columnar epithelial cell function [22]. These data point to further avenues for investigation of the specific nature of inflammatory, catabolic, and cytoskeletal responses in circulating immune cells in smokers.…”
Section: Discussionsupporting
confidence: 59%
“…Knockdown of c-Yes by ϳ75% did not affect the expression of several actin regulatory proteins, including 1) Arp3 and N-WASP, which are known to induce branched actin polymerization (11,22,49), 2) actin-binding protein drebrin E, which is known to recruit Arp3 to the BTB to elicit its restructuring at stage VIII of the epithelial cycle (4,34), and 3) Eps8, an actin barbed-end capping and bundling protein in the testis ( Fig. 2A) (2,37).…”
Section: Knockdown Of C-yes In Sertoli Cells By Rnai Accelerates Actimentioning
confidence: 97%
“…Drebrin is a neuronally expressed actin filament binding protein that has been involved in the regulation of neuronal morphology (Dun and Chilton, 2010; Dun et al, 2012). Drebrin can bundle actin filaments (Worth et al, 2013), regulate the binding of additional actin binding proteins to filaments (reviewed in Dun and Chilton, 2010) and importantly can also directly associate with microtubule plus tips through the end binding (EB) proteins (Geraldo et al, 2008; Bazellières et al, 2012). While there are multiple possible molecules involved in branching that have the potential to bind actin filaments and microtubules and thus serve as coordinators between these two cytoskeletal systems, no study to date has simultaneously addressed the role of any of these molecules in the regulation of the both the actin and microtubule cytoskeleton during branching.…”
Section: Introductionmentioning
confidence: 99%